Multihop Routing Implementation On Fire And Gas Leakage Detection System - Mulia, Benediktus Kevin; Ichsan, Mochammad Hannats Hanafi; Primananda , Rakhmadhany (Faculty of Computer Science (FILKOM) Brawijaya University, 2022)
Fires in the house occur due to several things, such as an electrical short circuit, and another cause is a gas leak from the LPG cylinder. This fire is caused by a lack of security in the house and public knowledge, the dangers of gas levels leaking from LPG gas cylinders, the presence of small fires, and temperatures too high due to these. Fire detectors and LPG gas leaks are provided in the home environment. This detection includes preventive efforts before a fire occurs and can be extinguished immediately. The method of the fire and gas leak detection prototype using the MQ-6 sensor, fire sensor and DHT-22 temperature sensor is multihop routing. This method was chosen because of the large number of sensors used, and in this prototype, there will be five sensor nodes and one sink node. With multihop routing, the prototype of this tool can be placed in various places and is faster in detecting fires if they occur in homes. This method is also used because it can send detection results from one sensor node to the sink node to the website database and the delivery time between these nodes is very short so that fires can be prevented and handled quickly. The test results of the fire sensor used to detect fire obtained an accuracy of 100%, and the detection distance of the fire was between 20 to 100 cm. In data transmission, the number of nodes is 5. The data delivery result is the closest to the end node, the more considerable the amount of data sent, increasing relatively, from around 3017 milliseconds to 575387 milliseconds.